Influence of biochar amendments on the soil quality indicators of sandy loam soils under cassava–peanut cropping sequence in the semi-arid tropics of Northern Lombok, Indonesia - Sukartono, Sukartono; Kusumo, Bambang Hari; Suwardji, Suwardji; Bakti, Arifin Aria; Mahrup, Mahrup; Susilowati, Lolita Endang; Fahrudin, Fahrudin (Universitas Sebelas Maret, 2022)
Low nutrient retention and soil organic matter depletion are the major challenges of the cropping system in the sandy loam soils of Northern Lombok, Indonesia. A field experiment was conducted to evaluate the influence of biochar-based organic amendments on the soil quality of sandy loam soils under cassava (Manihot Esculenta, Crants)–peanut (Arachis Hypogeae L.) cropping sequence. The treatments were as follows: biochar (10 ton ha-1) and rice straw (3 ton ha-1) (B1); biochar (10 ton ha-1), cattle manure (10 ton ha-1), and rice straw (3 ton ha-1) (B2); biochar (10 ton ha-1) and cattle manure (10 ton ha-1) (B3); biochar (10 ton ha-1) and cattle manure (10 ton ha-1) plus rice straw mulch (3 ton ha-1) applied on surface soils (B4), and without organic amendments (B0) as control. Results showed that the biochar-based organic amendments significantly improved several soil quality indicators such as SOC, total N, available P, Ca, cation-exchange capacity (CEC), and aggregate stability but had no significant effect on pH, K, and Mg. Improvement in soil quality was strongly indicated by an increase in the growth and yield of cassava and peanuts. Treatments B1, B2, B3, and B4 generally had a comparable effect on soil parameters and tended to improve the growth and yield of cassava and peanuts. Cassava was responsive to treatments B2 (biochar, cattle manure, and rice straw) and B3 (biochar and cattle manure) with its actual yield of 27 tons ha−1, which is a 40% increase compared with that in the control. As a secondary crop growing after cassava, peanuts also exhibited higher yields in all amended plots compared with that in the control. The highest yield was obtained in B2 (1.38 ton ha−1), followed by B4 (1.36 ton ha−1), B1 (1.33 ton ha−1), and B3 (1.25 ton ha−1). In conclusion, the incorporation of biochar, cattle manure, and crop residues (rice straw) into soils is a promising option to maintain soil quality and sustainably produce cassava and peanuts in the sandy loam soils of the semi-arid tropics of Lombok, Indonesia.